Physicochemical characterization on non-traditional flours and their application in cereals bars (Research, Society and Development, 2021)
Processing passion fruit generates a large amount of waste, wasting nutrients that could be used as an alternative for the production of non-traditional flours. The aim of the study was to prepare flour from passion fruit albedo, characterize it and compare it with commercial flours, in addition to manufacturing cereal bars from albedo flour, minimizing the waste generated. The husks were donated by a local pulp industry, from which the albedo was extracted, which was dried in an air-circulation oven and then crushed to obtain the flour. Proximate analysis and flour color (albedo and commercial) were performed. Four formulations of cereal bars were prepared (Sample BC 01, without addition of passion fruit albedo flour, Sample BC 02, 3% of the flour, Sample BC 03, 7% of the flour and Sample BC 04 11% of the flour) and evaluated its composition and caloric value. Microbiological analyzes and acceptance and purchase intent tests were performed. It was observed that the flour produced had a high content of crude fiber (67.30%) and a low amount of lipids and moisture (0.40% and 7.52%), respectively, while the commercial flours analyzed also presented composition meeting the standards required by law, but with a greater amount of carbohydrate. Cereal bars met acceptability standards. In the sensory parameters, it was possible to observe that most tasters really liked and liked the bars a lot, stating that they would certainly buy the product. It is concluded that passion fruit flours can be used as an alternative ingredient in the development and enrichment of foods, favoring the reduction of agroindustry residues and bringing potential health benefits.